2022
DOI: 10.3390/app12178623
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Capacity and Coverage of Satellite IoT for Developing Countries Using a CubeSat

Abstract: Many regions in developing countries do not have any access to communication networks even though the number of devices connected through the Internet of Things (IoT) is increasing significantly. A small satellite platform could provide global network coverage in low Earth orbit to these remote locations at a low cost. This paper describes the overall mission architecture and the implementation of remote IoT using a 1U volume in 6U CubeSat platform named KITSUNE. In KITSUNE, one of the missions is to leverage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…The continuous development of technologies and the reduction in launch costs have allowed small satellites to be employed in a wide range of missions. Scientific exploration [1], disaster monitoring [2], data collection systems [3], telecommunications [4], and Earth observation [5] are some of the applications that have benefitted from the introduction of small satellites, which can be deployed in large flocks of inexpensive craft, thus guaranteeing short revisit times and global coverage.…”
Section: Small Satellite Missionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuous development of technologies and the reduction in launch costs have allowed small satellites to be employed in a wide range of missions. Scientific exploration [1], disaster monitoring [2], data collection systems [3], telecommunications [4], and Earth observation [5] are some of the applications that have benefitted from the introduction of small satellites, which can be deployed in large flocks of inexpensive craft, thus guaranteeing short revisit times and global coverage.…”
Section: Small Satellite Missionsmentioning
confidence: 99%
“…An example of a real small satellite mission is reported in [3], which describes the capability and coverage of a satellite-based IoT network for providing remote data collection services to several developing countries. The system is based on a single CubeSat unit on board the KITSUNE satellite, a 6U CubeSat, and on a network of ground-based terminals.…”
Section: Small Satellite Missionsmentioning
confidence: 99%
“…En la actualidad varios desarrollos espaciales hacen uso de estas tecnologías, uno de los más recientes es el ideado por Julián Fernández, un adolescente que propuso la idea de enviar un PicoSat de 250 gramos que emplea la tecnología LoRa y de código abierto, para logar comunicaciones con satélites pequeños de experimentación. Para ello creó la empresa FOSSAAT [3] y con el apoyo de start ups y crowfunding, permitió poner en el espacio a FossaSat-1, el 12 de junio de 2019, el primer satélite LoRa basado en el estándar PocketQube para CubeSat que tienen un tamaño de 5x5x5cm. Ésta primera experiencia permitió que miles de datos de telemetría sean recibidos por estaciones terrenas en muchas partes del planeta [4].…”
Section: Introductionunclassified
“…In this perspective, the last years of research have shown how innovative communication systems and Radio-Frequency (RF) systems have been applied to new mission envelopes for aircraft and spacecraft. In particular, the utilization of Spread Spectrum (SS) and Internet-of-Things (IoT) technologies, such as Long Range (LoRa) transmitters, for satellite-based instrumentation tracking has been investigated with multiple demonstrator missions [25], such as KITSUNE [26,27], with the implementation of TinyGS networks [28]. The same technologies have been adapted for experimentation on-board a nano-satellite for monitoring wildlife in Kenya.…”
Section: Introductionmentioning
confidence: 99%